Odpowiedzi

2010-03-15T18:34:53+01:00
Wyłącz wspólny czynnik przed nawias.

5x + 10y =5(x+2y)
4m + 4 =4(m+1)
3a - 3 =3(a-1)
5xy - x = x(5y-1)

;))
Najlepsza Odpowiedź!
2010-03-15T18:35:20+01:00
3b(y-2)
2a(5a-b)
6(a-4b+5c)
x(x²-2x+x)


5(x+2y)
4(m+1)
3(a-1)
x(5y-1)
  • Użytkownik Zadane
2010-03-15T18:38:04+01:00
Przedstaw w postaci iloczynu.
3by - 6b =3(by-2b)
10a² - 2ab = 2a(5a-b)
6a - 24b + 30c =6(a-4b+5c)
x³ - 2x² + x =x(x²-2x)

Wyłącz wspólny czynnik przed nawias.
5x + 10y =5(x+2y)
4m + 4 =4(m+1)
3a - 3 =3(a-1)
5xy - x = x(5y-1)